Endometrial cancer and adiponectin - Bieńkiewicz, Jan; Romanowicz-Makowska, Hanna; Malinowski, Andrzej (Menopause Review/Przegląd Menopauzalny, 2012)
Endometrial cancer (EC) is one of the most common gynecologic malignancies in developed countries. Both histology and clinical practice divide ECs into two independent subgroups: type I, or endometrioid endometrial carcinoma – EEC, which is more frequent and carries a generally better prognosis, and type II – non-endometrioid endometrial carcinoma – NEEC – a disease of much lower morbidity, still not understood well enough and of rather grave prognosis. Among many well-established risk factors that determine development of EC, science has named a classic trio: obesity, diabetes and arterial hypertension. Nevertheless, not more than a half of EC patients display characteristic risk factors. Therefore, current scientific efforts are made to understand this malignancy in a more thorough way: to achieve that research has to be brought deep into cellular and molecular levels. A contemporary approach to EC demands a more complex insight into sophisticated mechanisms linking extracellular signaling within the insulin-like growth factor system and adipose tissue metabolism. Recent data on protein products of adipocytes indicate adiponectin as a potential clue factor to understand the relation between obesity, insulin resistance and EC. Present outcomes show that hypoadiponectinemia is an indisputable risk factor for developing EC, particularly in pre- and perimenopausal obese women. This paper shows an up-to-date literature review on the role of adiponectin in the compound pathology of EC.